2020
DOI: 10.3390/ijms21041375
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Between Stress, Mental Disorders, and Epigenetic Regulation of BDNF

Abstract: Brain-derived neurotrophic factor (BDNF), a critical member of the neurotrophic family, plays an important role in multiple stress-related mental disorders. Although alterations in BDNF in multiple brain regions of individuals experiencing stress have been demonstrated in previous studies, it appears that a set of elements are involved in the complex regulation. In this review, we summarize the specific brain regions with altered BDNF expression during stress exposure. How various environmental factors, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 173 publications
(194 reference statements)
1
57
0
2
Order By: Relevance
“…Accordingly, accumulating data indicated the negative effects of chronic stress on Bdnf expression ( Miao et al, 2020 ), as well as the role of Bdnf in promoting resilience ( Krishnan et al, 2007 ; Taliaz et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, accumulating data indicated the negative effects of chronic stress on Bdnf expression ( Miao et al, 2020 ), as well as the role of Bdnf in promoting resilience ( Krishnan et al, 2007 ; Taliaz et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in animal models of stress and depression revealed a decrease in Bdnf hippocampal mRNA levels, mediated by long-lasting methylation and acetylation changes in the promoter regions of Bdnf that were induced from perinatal exposure to methylmercury [ 101 ] or chronic social defeat stress conditions [ 102 , 103 ]. Moreover, in patients with depression, there was a significant decrease in BNDF protein levels compared to controls [ 104 ], while administration of antidepressants, such as selective serotonin reuptake inhibitors, stimulated BDNF expression and reversed the symptoms of depression [ 105 ].…”
Section: Epigenetic Changes and Stress-related Disordersmentioning
confidence: 99%
“…Depressive disorder is associated with marked reduced levels of BDNF, both in humans and different animal models including chronic unpredictable mild stress (CUMS) paradigm. Depression is also accompanied by altered hippocampal or frontal brain structures and it has been consistently suggested that this might be a consequence of lowered BDNF [ 20 , 21 , 22 , 23 , 24 ]. In addition, BDNF knockdown rats showed depressive-like behaviour and had reduced neurogenesis in the hippocampus [ 25 ].…”
Section: Introductionmentioning
confidence: 99%